The Effect of Core Stability Training on Body Composition and Lipoprotein in Menopausal Older Women - Rahimeh Mehdizadeh (Sālmand, 2015)
Objectives Unfavorable changes occur in the body composition and lipoprotein that are related to the loss of estrogen levels after menopause. We aimed to study the effect of core stability training on body composition and lipoprotein in menopausal older women. Methods & Materials In this semi-empirical study, 23 older women living in a nursing home in Shahrood were selected purposively, during 2012 and divided randomly in to experimental (n=13) and control (n=10) groups. The participants underwent a supervised exercise protocol during 24 weeks (3 days/week, 45-60 min/day). In each session, core stability training (strength and endurance) was done for 25-30 minutes.  Plasma lipoprotein and anthropometric indexes of obesity consisting of body weight, Body Mass Index (BMI) and Waist Circumference (WC) were measured before and after exercise training program. Results We found a significant difference in WC before and after the intervention in the experimental group (P=0.03). Moreover, after training, plasma total cholesterol level changed significantly be-tween the two groups (P=0.007) and changes in other components of lipoprotein were not significant. Conclusion Core stability training could improve body composition and some components of lipoprotein in menopausal older women.